Hadith #3205 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Kathir bin Zayd al-'Aslmy كثير بن زيد الأسلمي; Sa'id bin Salm al-Qudah سعيد بن سالم القداح (Sunan Abi Dawud)
On the authority of his father: The Messenger of Allah (ﷺ) commanded us to proceed to the land of Negus. Mentioning the rest of the tradition he said that Negus said: I bear witness that he is the Messenger of Allah (ﷺ), and it is he about whom Christ son of Mary gave good news. It I were not in the land which I am, I would come to him and carry his shoes.
Grade: Da'if